Socioeconomic and Cultural Determinants of Early Childhood Feeding Practices in Indonesia - Pranita, Rani Fitri (Journal of Global Nutrition, 2025)
Infant and young child feeding practices among children aged 6–23 months remain a major challenge in Indonesia due to social, economic, cultural inequalities and regional contextual disparities. These conditions directly affect the achievement of Infant and Young Child Feeding indicators, particularly the Minimum Acceptable Diet (MAD). This study aimed to review and synthesize scientific evidence on the socioeconomic and contextual determinants of feeding practices among children aged 6–23 months in Indonesia. This study employed a literature review design using a narrative synthesis approach. A systematic search was conducted in PubMed, ScienceDirect, Google Scholar, and Garuda databases for publications from 2020 to 2024. Articles were selected based on predefined inclusion and exclusion criteria and analyzed descriptively. The results of this review identified nine eligible articles, which consistently indicated that household economic status was the most influential determinant of child feeding practices. Maternal education, area of residence, antenatal care visits, paternal involvement, and access to media and the internet were also associated with variations in MAD achievement. Children from wealthier households and those living in urban areas were more likely to experience better feeding practices. In conclusion, infant and young child feeding practices in Indonesia are strongly shaped by socioeconomic factors and environmental context. It is recommended that nutrition interventions be designed in an integrated manner, with a focus on reducing socioeconomic inequalities, strengthening family roles, and optimizing health services and nutrition-related information channels.